Environmental governance and social learning: towards more reflexive interactions - Jacobi, Pedro Roberto; de Souza, Daniele Tubino (Desenvolvimento e Meio Ambiente, 2021)
Facing the increasing complexity of social and environmental issues, environmental governance configurations are required to adopt increasingly collaborative strategies and reflexive learning oriented practices. The goal of this paper is to present a theoretical discussion about environmental governance and the contribution of the social learning approach to expand the reflexivity potential of multi-stakeholder interaction spaces in governance processes. We argue that social learning practices, understood as interactive and reflective, can broaden the critical responsiveness of participating in environmental governance systems. Social learning-oriented processes are based on the promotion of dialogic spaces in which participants can learn from the diverse views present in the group and critically reflect on the assumptions that underlie decision making, thus creating possibilities for the emergence of innovative practices and new social configurations. We conclude that social learning processes driven by the stakeholders interactions in environmental governance spaces tend to broaden the ability of participants to critically evaluate the governance structure itself, in order to foster arrangements that can effectively promote practices for sustainability.